2008
DOI: 10.1159/000185828
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of N-Acetylcysteine on Proteinuria and Markers of Tubular Injury in Non-Diabetic Patients with Chronic Kidney Disease

Abstract: Background: Inhibition of the renin-angiotensin-aldosterone system with angiotensin-converting enzyme inhibitors (ACEI) and/or angiotensin II subtype 1 receptor antagonists (ARB) constitutes a strategy in the management of patients with chronic kidney disease. There is still no optimal therapy which can stop the progression of chronic kidney disease. Antioxidants such as N-acetylcysteine (NAC) have been reported as a promising strategy in this field. Methods: In a placebo-controlled, randomized, open, 2-period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 99 publications
0
16
0
1
Order By: Relevance
“…Wittstock et al demonstrated administration of NAC during dialysis session significantly improved arterial vascular reactivity in end stage CKD patients (NAC dosage: 5 gram IV during dialysis session) [60]. Contrary to that Renke et al had reported, NAC had no effect on proteinuria and markers of tubular and renal fibrosis in non-diabetic CKD patients (NAC dosage: 1200 mg/day orally) [61]. …”
Section: Discussionmentioning
confidence: 99%
“…Wittstock et al demonstrated administration of NAC during dialysis session significantly improved arterial vascular reactivity in end stage CKD patients (NAC dosage: 5 gram IV during dialysis session) [60]. Contrary to that Renke et al had reported, NAC had no effect on proteinuria and markers of tubular and renal fibrosis in non-diabetic CKD patients (NAC dosage: 1200 mg/day orally) [61]. …”
Section: Discussionmentioning
confidence: 99%
“…CD, collecting duct; DT, distal tubule; mTAL, medullary thick ascending limb; PT, proximal tubule. (4,135,163) and cultured human PTCs (332), its use for the treatment of patients with CKD has been disappointing (186,252). However, in patients with end-stage renal disease, NAC did reduce inflammatory cytokines (119,198) while improving early outcomes in kidney transplant recipients (54).…”
Section: N-acetylcysteinementioning
confidence: 99%
“…Redox Signal. 20,[164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182] …”
Section: Introductionunclassified